(untitled) (Physical Education, Health and Social Sciences, 2026)
This paper provides a comprehensive psycholinguistic analysis of language processing in multilingual societies, shifting from monolingual-centric models to viewing multilingualism as the normative human condition. It examines core mechanisms including nonselective lexical access across languages, evidenced by cognate facilitation and parallel activation in models such as the Revised Hierarchical Model (RHM), BIA+, and Multilink. Cognitive control processes, particularly inhibitory control and adaptive mechanisms in code-switching contexts, are explored through frameworks like the Inhibitory Control model and Adaptive Control Hypothesis. Neurobiological evidence highlights structural plasticity, overlapping neural networks modulated by proficiency and age of acquisition, and modality-dependent processing in diglossic environments such as Arabic. Additional topics include suprasegmental (tonal) cross-linguistic influences and models of third language (L3) acquisition emphasizing selective or typological transfer. The discussion extends to educational implications, supporting multilingual pedagogies and translanguaging to promote equity and cognitive benefits. Despite advances, persistent gaps remain in research on non-Indo-European languages and low-resource contexts, underscoring the need for inclusive, globally representative studies and equitable NLP development. Overall, multilingualism reveals fundamental interactions between language, cognition, and society, offering critical insights into the adaptive architecture of the human language system.